14th International Seminar NUTAU: Urban Soundscape - Michalski, Ranny Loureiro Xavier Nascimento (Acústica e Vibrações, 2023)
This insert covers the 14th NUTAU International Seminar, focused on urban soundscape. Held in December 2022, the event promoted discussions on technological innovations and urban planning and design practices, highlighting lectures, round tables, and presentations by national and international experts. The seminar reaffirmed the importance of multidisciplinary collaboration.